National Early Warning Score 2 (NEWS2) to identify inpatient COVID-19 deterioration: a retrospective analysis. Issue 2 (2021) - Baker, Kenneth F; Duncan, Christopher JA; Hanrath, Aidan T; Loeff, Ina Schim van der; Kay, Lesley J; Back, Jonathan
No abstract available